Sistem Pendukung Keputusan Penerima Bantuan Program Keluarga Harapan (PKH) Menggunakan Metode Simple Multi Attribute Rating Technique (SMART) (Studi Kasus: Desa Kemudi) - Alifia Zaida Nurmaya; Budi Harijanto; Kadek Suarjuna Batubulan (Jurnal Ilmiah Informatika, 2022)
There are many government assistance programs, one of which is the Family Hope Program (PKH), which is a social assistance program aimed at poor families with certain conditions. The Family Hope Program is expected to be able to ease the burden on families. A large number of poor families in the village will make it difficult for village officials to select families who are entitled to receive assistance. However, sometimes aid program are not well targeted, thus triggering a sense of injustice for other poor families. The data collection process for poor families and the selection process is still done manually, thus allowing for errors in entering data and sometimes the selection results do not match or do not meet the criteria for recipients of assistance, it will lead to misunderstandings between the community and village officials. Therefore , to prevent the recurrence of this problem, it is necessary to have an information system with a decision support system to provide recommendations for PKH beneficiary families by predetermined criteria. The decision support system using the Simple Multi Attribute Rating Technique (SMART) method is expected to provide the best recommendations with criteria that have criteria values ​​and weights. The results of the application of the Simple Multi Attribute Rating Technique method on decision support system resulted in an accuracy value of 98%, so this system can be applied in Kemudi Village to assist village officials in the process of selecting the recipients of the Family Hope Program.